2011
DOI: 10.5194/acp-11-4505-2011
|View full text |Cite
|
Sign up to set email alerts
|

Detailed heterogeneous oxidation of soot surfaces in a particle-resolved aerosol model

Abstract: Abstract.Using the particle-resolved aerosol model PartMC-MOSAIC, we simulate the heterogeneous oxidation of a monolayer of polycyclic aromatic hydrocarbons (PAHs) on soot particles in an urban atmosphere. We focus on the interaction of the major atmospheric oxidants (O 3 , NO 2 , OH, and NO 3 ) with PAHs and include competitive co-adsorption of water vapour for a range of atmospheric conditions. For the first time detailed heterogeneous chemistry based on the Pöschl-Rudich-Ammann (PRA) framework is modelled o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 79 publications
2
43
0
Order By: Relevance
“…This model explicitly resolves the composition of individual particles in a given aerosol population and is therefore uniquely suited to investigate the evolution of particle mixing states and the associated particle properties. PartMC-MOSAIC has been used for detailed studies on the particle level, for example to derive aging time-scales of black carbon aerosol (Riemer et al, 2010), to investigate the heterogeneous oxidation of soot surfaces (Kaiser et al, 2011), to quantify the impacts of black carbon mixing state on black carbon nucleation scavenging (Ching et al, 2012), and to explore the sensitivity of cloud condensation nuclei activity to particle characteristics at emission (Fierce et al, 2013). It was also used as a modeling tool to explain the diurnal variations of aerosol hygroscopicity and the mixing state of light-absorbing carbonaceous material in the North China Plain (Liu et al, 2011;Ma et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This model explicitly resolves the composition of individual particles in a given aerosol population and is therefore uniquely suited to investigate the evolution of particle mixing states and the associated particle properties. PartMC-MOSAIC has been used for detailed studies on the particle level, for example to derive aging time-scales of black carbon aerosol (Riemer et al, 2010), to investigate the heterogeneous oxidation of soot surfaces (Kaiser et al, 2011), to quantify the impacts of black carbon mixing state on black carbon nucleation scavenging (Ching et al, 2012), and to explore the sensitivity of cloud condensation nuclei activity to particle characteristics at emission (Fierce et al, 2013). It was also used as a modeling tool to explain the diurnal variations of aerosol hygroscopicity and the mixing state of light-absorbing carbonaceous material in the North China Plain (Liu et al, 2011;Ma et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Using K2-SURF Shiraiwa et al (2011b) showed that long-lived reactive oxygen intermediates are formed in the reaction of ozone with aerosol particles. Springmann et al (2009) and Kaiser et al (2011) demonstrated the applicability and usefulness of the PRA framework in an urban plume box model of the degradation of benzo [a]pyrene on soot by ozone and nitrogen dioxide. Pfrang et al (2010) developed a kinetic double-layer model coupling aerosol surface and bulk chemistry (K2-SUB), in which mass transport and chemical reactions in the bulk are not explicitly resolved but represented by a reacto-diffusive flux analogous to traditional resistormodel formulations.…”
mentioning
confidence: 99%
“…The synthesis of monofunctional alkyl nitrates can be performed via several methods (Boschan et al, 1955), including nitration of alkyl halides with silver nitrate, direct nitration of alcohols or alkanes with nitric acid (Luxenhofer et al, 1996;Woidich et al, 1999), or treatment of alcohols with dinitrogen pentoxide (Kames et al, 1993). Techniques for the synthesis of multifunctional nitrates (in particular, hydroxynitrates) have been described in previous reports (Muthuramu et al, 1993;Kastler and Ballschmiter, 1998;Werner et al, 1999;Treves et al, 2000).…”
Section: Organic Nitrate Standardsmentioning
confidence: 99%